Penggunaan Air Kelapa sebagai Sumber Nutrisi Alternatif pada Pertumbuhan Kangkung Darat (Ipomoea reptans Poir.) - Zulpan Efendi Nasution; Siti Hardianti Wahyuni; Parmanoan (Yayasan Perguruan Kampus, 2024)
The fermentation process with a mixture of coconut water as ZPT and EM4 as a bioactivator. The purpose of this study is to determine the effect of administering several doses of coconut water and enriched with EM4. This study used a Complete Random Design (RAL) with 6 treatments, namely manure and urea (positive control), negative control (no fertilizer), A1 (Coconut Water Fermentation) 10%, A2 20%, A3 30%, and A4 40%. Data analysis using ANOVA was followed by DMRT tests with the SPSS application. The results showed that Based on the results of the study, it can be concluded that the fermentation of coconut water enriched with EM4 has a real effect on the parameters of leaf area and plant height (28 HST) and the number of leaves on the plant (28 HST). The dose of coconut water that gave the best results for plant growth in this study was P4,